(untitled) - Burns, Ed (New York, 2014)
Optimize productivity while reducing risk and complexity by adopting a highly agile, "automate everything" software design philosophy. Hudson Continuous Integration in Practice shows you how to streamline and stabilize each process in your development lifecycle. Get expert tips for deploying a Hudson server, managing test and reporting frameworks, using source code management (SCM), and incorporating third-party CI tools. Distributed builds, plugin development, and system administration are also covered in this Oracle Press guide.Install, configure, and secure Hudson.Automate build, integration, release, and deployment processes. Set up jobs and add SCM from the Web-based GUI.Administer QA tools, issue trackers, and build notifiers. Incorporate IDEs, browsers, desktops, and mobile device.Publish Hudson build artifacts to Oracle Middleware utilities.Work with plug-in manager and develop your own plugins.Create custom dashboards and organize your jobs with views.Develop a custom publisher, recorder, and notifier for your jobs
Keywords: Open source software,Computer software,Phần mềm máy tính,Phần mềm mã nguồn mở,Phần mềm máy tính,Computer software; Quality control,Phát triển,Kiểm soát chất lượng,Development